HUBUNGGAN ANTARA KEKUATAN OTOT KAKI TERHADAP KETETEPAN HASIL JUMPT SHOOT PADA PERMAINAN BOLA BASKET DI TEAM BARA PUTRA LUBUKLINGGAU - Hengky Remora; Wawan Syafutra (LP4MK STKIP PGRI Lubuklinggau, 2022)
The purpose of this study was to find out whether there is a relationship between leg muscle strength and the accuracy of the Jump Shoot results in a basketball game at the Bara Putra Lubuklinggau club in 2021. The variables in this study were leg muscle strength as the independent variable and the results of the Jump Shoot as the dependent variable. The sample in this study used the entire population, namely 20 athletes. The method used in this study is the correlational method. The data collection technique consists of documentation, test techniques, data analysis techniques, and hypothesis testing used, namely the